Concentration effect of DMSO-dry bonding on the stability of etch-and-rinse bonds - Ismail Omar Abdelaziz; Stape Thiago Henrique Scarabello; Tezvergil-Mutluay Arzu (Elsevier Inc., 2025)
OBJECTIVES
To examine whether lower dimethyl sulfoxide (DMSO) concentrations would affect long-term bond stability of simplified or multistep water-based adhesives to dry-etched dentin.
METHODS
H3PO4-etched mid-coronal dentin surfaces from human molars were randomly blot- or air-dried for 30 s and pretreated or not with 5 or 50 % (v/v) ethanolic DMSO solutions. Untreated samples served as control. Samples were bonded with a two-step or a three-step etch-and-rinse adhesive. Restored crown segments (n = 5/group) were stored in distilled water for 24 h and sectioned for microtensile bond strength testing. Resin-dentin beams (0.8 mm2) were tested under tension until fracture (0.5 mm/min) after 24 h and one year of storage in artificial saliva at 37 °C. Nanoleakage evaluation and hybrid layer characterization were performed by SEM. Bond strength data was examined by three-way ANOVA followed by the Tukey test (α = 0.05).\nDry bonding produced significantly lower bond strengths than conventional wet bonding for both water-based adhesive systems (p < 0.05). DMSO-dry bonding restored bond strengths and reduced nanoleakage levels, regardless of adhesive type or DMSO concentration (p < 0.05). Bond strengths of DMSO-dry bonded samples were not significantly affected by long-term ageing regardless of adhesive type or DMSO concentration (p < 0.05).
SIGNIFICANCE
Although bonding methacrylate-based resins to etched dentin is normally performed under wet conditions, hybridization of air-dried collagen can outperform conventional wet bonding by employing water-free DMSO solutions with concentrations as low as 5 %. Reduced moisture-related technique sensitivity, higher bonding performance and improved hybrid layer stability may contribute to extend the service life of resin-dentin bonding.